Prevalencia de los defectos de desarrollo del esmalte y su asociación con factores predisponentes en niños de 6 a 12 años de la I.E. Santo cristo de Bagazán - Rengifo Panaifo, Carol Mishel (2025)
Objective: To determine the prevalence of developmental enamel defects (DED) and their association with predisposing factors in children aged 6 to 12 years from “Santo Cristo de Bagazán” School, Belén district. Materials and methods: A quantitative, non-experimental, cross-sectional, and correlational study was conducted with a population of 408 schoolchildren. The Modified DDE Index and Dean’s Index were used for clinical diagnosis. A questionnaire was applied to parents to collect prenatal, perinatal, and postnatal background information. Data were analyzed using SPSS v27 software and Pearson’s Chi-square test, with a significance level of p < 0.05. Results: The prevalence of DED was 41.4%, with demarcated opacities (29.4%) being the most frequent defect. Significant associations were found between DED and episodes of diseases (p = 0.001), birth weight (p = 0.001), and breastfeeding (p = 0.001). No significant association was found with maternal age (p = 0.216) or educational level (p = 0.640). Conclusion: Developmental enamel defects are common among schoolchildren in Belén and are mainly associated with systemic and nutritional factors during early childhood. Preventive dental care and maternal–child health programs should be reinforced at the primary care level.